DESAIN PEMBELAJARAN DISASSURE BERBASIS KETERAMPILAN ABAD 21 DALAM PEMBELAJARAN BAHASA JEPANG - Nevia Octa Permatasari (Universitas Negeri Surabaya, 2020)
This research is motivated by the need for the ability to master 21st century skills in line with the changing times. Therefore, language learning is needed for an instructional model that adjusts to the 21st century skills. An effective and fun learning design is needed in learning Japanese to make learners more active and motivated in learning the language. This research is a literature study. The purpose of this study was to describe how to illustrate and apply the Discovery Learning and ASSURE learning models by adding 21st century skills to Japanese grammar learning.The method was used was qualitative approach. This type of research is descriptive research. This study aims to describe an instructional design model for the development of a learning model that modifies Discovery Learning and ASSURE with the addition of 21st century skills, such as critical thinking, collaboration and communication. This research finding are the student centered instruction model that adjust with the 21st century skills, and the teacher as facilitators encourage learners to be responsible for the learning process they are doing so that learners can find the concept of their own sentence patterns, practice critical thinking , communication and collaboration skills.